Recent advances toward the development of Hsp90 C-terminal inhibitors. (15th January 2023) - Amatya, Eva; Blagg, Brian S.J.
Graphical abstract: Abstract: Heat shock protein 90 (Hsp90) is a dynamic protein which serves to ensure proper folding of nascent client proteins, regulate transcriptional responses to environmental stress and guide misfolded and damaged proteins to destruction via ubiquitin proteasome pathway. Recent advances in the field of Hsp90 have been made through development of isoform selective inhibitors, Hsp90 C-terminal inhibitors and disruption of protein–protein interactions. These approaches have led to alleviation of adverse off-target effects caused by pan-inhibition of Hsp90 using N -terminal inhibitors. In this review, we provide an overview of relevant advances on targeting the Hsp90 C-terminal Domain (CTD) and the development of Hsp90 C-terminal inhibitors (CTIs) since 2015.